The household as an Economic Unit in Arctic Aboriginal Communities and its Measurement by Means of a Comprehensive survey. - Peter J. Usher; Duhaime, Gérard; Searles, Edmund (Springer, 2024)
Northern aboriginal communities are widely recognized as having mixed, subsistence-based economies. The chief characteristic of this economy, aside from the contribution of subsistence harvesting and related activities to household well-being, is that the household operates as a "micro-enterprise" that is the basic unit of production as well as consumption. This economic form has persisted into the present day, contrary to the predictions of many social scientists and policy-makers. This paper outlines a model of the household in mixed, subsistence-based economies, and describes its characteristics and activities. While the discussion focuses on northern Canada, the model is thought to apply generally in the circumpolar North. Quantitative measurement of northern aboriginal household characteristics and activities has been limited, however, because national and regional data collection systems are not designed specifically to capture these phenomena. The model is therefore based primarily on the results of in-depth case studies, and the systematic measurement of subsistence harvesting. This paper describes the development, for the first time, of a questionnaire specifically designed to document quantitatively the key characteristics of the household economy as part of a comprehensive survey of living conditions in the circumpolar Arctic.